THE IMPORTANCE OF USING PERSONAL PROTECTIVE EQUIPMENT (PPE) IN THE TEXTILE INDUSTRY - Rodrigues, Alef Ruan do Rosario; de Lima, Cicero Hiago Queiroz; Barreto, Clarice Guilherme; Henrique, Daniele de Macedo; de Lima, Damião Rodrigo Queiroz; Silva, Gabriel Eduardo dos Santos; Gomes, Iverton Rodrigo Barbosa; da Silva, Matheus Henrique Fonseca; de Macedo Neto, Miguel Cabral (Seven Editora, 2026)
This paper discusses the importance of using Personal Protective Equipment (PPE) in the textile industry, a sector that presents specific occupational risks, such as exposure to textile dust, excessive noise, heat, chemicals, and machine accidents. The justification is based on the need to preserve the health and physical integrity of workers in the face of such risks. The objective is to analyze the degree of adherence to the use of PPE by textile industry workers and to identify the main factors that influence this practice. The methodology adopted involved field research with the application of questionnaires in factories located in the metropolitan region of Natal/RN, in addition to a literature review on regulatory standards. The results reveal that, although Personal Protective Equipment is available, its continuous use is still compromised by factors such as discomfort, lack of knowledge of the risks, and absence of specific training. It is concluded that the effectiveness of PPE depends on integrated actions involving education, inspection, and encouragement of a safety culture in the factory environment.